Anti-representationalism in language development research: A commentary on Ambridge (2020). Issue 5 (October 2020) - Knabe, Melina L.; Vlach, Haley A.
Ambridge argues that there is widespread agreement among child language researchers that learners store linguistic abstractions. In this commentary the authors first argue that this assumption is incorrect; anti-representationalist/exemplar views are pervasive in theories of child language. Next, the authors outline what has been learned from this body of work, including insights into mechanisms underlying language learning. Interestingly, some of these mechanisms are at odds with counterarguments in Ambridge, such as the finding that forgetting is a critical process of language.